SafeTalk: Pengembangan Sistem Informasi Pelaporan Kasus Pelecehan Seksual dan Bullying untuk Mengatasi Perilaku Kekerasan di Sekolah - Wahyu Hidayat M; Nur Azizah Ayu Safanah; Rifqa Awalia; Muh Akbar B; Ardi Ansya (Indonesian Technology and Education Journal, 2023)
The best place for children to learn and explore their creative potential is in the classroom, allowing them to interact positively with their surroundings. Education differs from sex education in that it refers to the process by which people acquire knowledge and skills that can help them realize their potential and live a better life. Sex education is still seen as a taboo and receives little praise in society. The increase in cases of sexual violence and bullying on campuses and in schools shows that this problem is still poorly understood and there is a lack of resources to help affected individuals. In this work, the author tries to develop an information system that can function as a system that helps victims of violence by providing sexual and anti-bullying education. A total of 37 students and instructors based in Makassar became the sample for this study. Information gathering conducted using a survey distributed via Google Form and literature review as a method of data collection. Black Box Testing is used to test the designed system, checking the functionality of each feature. According to research findings, SafeTalk is quite useful and has a positive impact on its users